The influence of exterior surface solar absorptivity on thermal characteristics and optimum insulation thickness - Ozel, Meral (Pergamon-Elsevier Science Ltd, 2012)
In this study, the influence of exterior surface solar absorptivity on the thermal characteristics and optimum insulation thickness is investigated under dynamic thermal conditions. Numerical model based on an implicit finite difference method under steady periodic conditions is used to determine thermal characteristics such as yearly cooling and heating transmission loads, yearly averaged time lag and decrement factor. Later, these loads are used as inputs to an economic model for the determination of the optimum insulation thickness. The investigation is carried out for a south-facing wall in the climatic conditions of Elazig, Turkey. Solar absorptance of external surface is assumed to be varying from 0 to 1 with an increment of 0.2. Extruded polystyrene as insulation material is selected. As the absorptance increases, heating and total transmission loads decrease while cooling transmission load increase. It is seen that the increase rate in the cooling load ranges from 66.26% to 331.28% while reduction rates in the heating and total loads range from 6.72% to 33.65% and from 2.57% to 12.90%, respectively. The results show that for uninsulated and insulated walls, solar absorptivity has a great effect on the yearly transmission loads while it has a small effect on the yearly averaged time lag. On the other hand, decrement factor is almost unaffected by solar absorptance. The results also show that solar absorptivity has a very small effect on the optimum insulation thickness and payback period, but a more significant effect on energy savings. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Thermal characteristics; Optimum insulation thickness; Solar absorptivity; Finite difference method